The method of multi objective synthesis of stochastic robust control by multimass electromechanical systems under non-gausian random external disturbances - Kuznetsov, B. I.; Nikitina, T. B.; Bovdui, I. V.; Voloshko, O. V.; Kolomiets, V. V.; Kobylianskyi, B. B. (Національний технічний університет "Харківський політехнічний інститут", 2022)
Development of the method of multi objective synthesis of stochastic robust control by multimass electromechanical systems to satisfy various requirements for the operation of such systems in various modes under non-gausian random external disturbances. Methodology. The problem of multi objective synthesis of stochastic robust control by multimass electromechanical systems to satisfy various requirements for the operation of such systems in various modes under non-gausian random external disturbances solved based on the choosing of weight matrices in the robust control goal vector.The calculation of the target vector is performed based on the solution of the zero-sum vector antagonistic game. The components of the game payoff vector are variable quality indicators that are applied to the system operation in various modes. The calculation of the components of payoff vector game are performed based on the simulation of the initial system closed by the synthesized stochastic controllers in various operating modes and under various external influences and variations in the parameters of the uncertainty of the initial plant. Results. The results of multi objective synthesis of stochastic robust twomass electromechanical servo systems modes under non-gausian random external disturbances in which differences requirements for the operation of such systems in various modes were satisfied are given. Based on the results of modeling and experimental studies it is established, that with the help of synthesized robust nonlinear controllers, it is possible to improve of quality indicators of two-mass electromechanical servo system in comparison with the system with standard regulators. Originality. For the first time the method of multi objective synthesis of stochastic robust control by multimass electromechanical systems to satisfy various requirements for the operation of multimass systems in various modes is developed. Practical value. From the point of view of the practical implementation the possibility of solving the problem of multi objective synthesis of stochastic robust control systems to satisfy various requirements for the operation of multimass electromechanical systems in various modes is shown.

Розробка методу багатокритеріального синтезу стохастичного робастного керування багатомасовими електромеханічними системами для задоволення різноманітних вимог до роботи багатомасових систем в різних режимах при негаусових випадкових зовнішніх збуреннях. Методологія. Задача багатокритеріалного синтезу стохастичного робастного керування багатомасовими електромеханічними системами для задоволення різноманітних вимог до роботи систем в різних режимах при негаусових випадкових зовнішніх збуреннях вирішена на основі вибору вагових матриць у векторі цілі робастного керування. Обчислення вектору цілі виконується на основі рішення векторної антагоністичної гри з нульовою сумою. Компонентами вектора ціни ігри є показники якості, які пред'являються до роботи системи в різних режимах. Обчислення компонентів вектора ціни гри виконано на основі моделювання вихідної системи, замкненої синтезованими стохастичними регуляторами в різних режимах роботи та при різних зовнішніх впливах та варіаціях параметрів невизначеності вихідної системи. Результати. Наведено результати багатокритеріалного синтезу стохастичних робастних двомасових електромеханічних сервосистем при негаусових випадкових зовнішніх збуреннях, в яких задовольняються вимоги до роботи таких систем у різних режимах. На основі результатів моделювання та експериментальних досліджень встановлено, що за допомогою синтезованих стохастичних робастних регуляторів можна підвищити якісні показники двомасової електромеханічної сервосистеми в порівнянні з системою зі стандартними регуляторами. Оригінальність. Вперше розроблено метод багатокритеріального синтезу стохастичного робастного керування багатомасовими електромеханічними системами для задоволення різноманітних вимог до роботи таких систем у різних режимах. Практична цінність. З точки зору практичної реалізації, показано можливість вирішення задачі багатокритеріалного синтезу стохастичних робастних систем керування для задоволення різноманітних вимог до роботи багатомасових електромеханічних систем в різних режимах.
Keywords: multimass electromechanical systems; stochastic robust control; multi objective synthesis; zero-sum vector game solution; computer simulation; experimental research; багатомасові електромеханічні системи; стохастичне робастне керування; багатокритеріальний синтез; рішення векторної антагоністичної гри з нульовою сумою; комп’ютерне моделювання; експериментальні дослідження